Characterization of two novel butanol dehydrogenases involved in butanol degradation in syngas‐utilizing bacterium Clostridium ljungdahlii DSM 13528. (29th May 2013) - Tan, Yang; Liu, Juanjuan; Liu, Zhen; Li, Fuli
<x xml:space="preserve">Abstract</x> Syngas utilizing bacterium Clostridium ljungdahlii DSM 13528 is a promising platform organism for a whole variety of different biofuels and biochemicals production from syngas. During syngas fermentation, C. ljungdahlii DSM 13528 could convert butanol into butyrate, which significantly reduces productivity of butanol. However, there has been no any enzyme involved in the degradation of butanol characterized in C. ljungdahlii DSM 13528. In this study two genes, CLJU_c24880 and CLJU_c39950, encoding putative butanol dehydrogenase (designated as BDH1 and BDH2) were identified in the genome of C. ljungdahlii DSM 13528 and qRT‐PCR analysis showed the expression of bdh1 and bdh2 was significantly upregulated in the presence of 0.25% butanol. And the deduced amino acid sequence for BDH1 and BDH2 showed 69.85 and 68.04% identity with Clostridium acetobutylicum ADH1, respectively. Both BDH1 and BDH2 were oxygen‐sensitive and preferred NADP+ as cofactor and butanol as optimal substrate. The optimal temperature and pH for BDH1 were at 55 °C and pH 7.5 and specific activity was 18.07 ± 0.01 µmol min−1 mg−1. BDH2 was a thermoactive dehydrogenase with maximum activity at 65 °C and at pH 7.0. The specific activity for BDH2 was 11.21 ± 0.02 µmol min−1 mg−1. This study provided important information for understanding the molecular mechanism of butanol degradation and determining the targets for gene knockout to improve the productivity of butanol from syngas in C. ljungdahlii DSM 13528 in future.